PEMENTASAN DRAMA DENGAN PENDEKATAN PROJECT BASED LEARNING SEBAGAI UPAYA PEMBEKALAN ARTISTIK PERTUNJUKAN BAGI MAHASISWA CALON GURU - Akhmad fatoni; Achmad Dipoyono; Deni Mustopa; Rani Jayanti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2020)
This research was conducted because the trigger for theater performances in Mojokerto has always decreased from year to year, especially school theaters. The student theater festival, which is held annually, has not been held for two years. The trigger for the school to allow and finance the show did not exist. The purpose of this research is to find a solution to the decreasing productivity of performances in Mojokerto. The method used is a single case study method. This case study stage uses a